Stiffness and strength analysis of hybrid adhesive bonded – resistance spot welded sandwich samples by means of virtual FE testing. Issue 5 (1st June 2019) - Weiland, J.; Debruyne, S.; Vandepitte, D.; Pulm, M.; Schiebahn, A.; Reisgen, U.
ABSTRACT: Hybrid adhesive bonding is widely applied in industry nowadays. Whereas combinations of mechanical fastening and structural adhesive bonding are being used for a long time, hybrid bonds, which combine (resistance spot) welding and adhesive bonding, are a quite recent development. Although this technique of hybrid joining yields structures with excellent mechanical characteristics concerning static and dynamic stiffness and strength, it is hard to numerically predict these characteristics accurately. This originates from the fact that usually only some data is known on the stiffness and strength of the adhesive and spot welds but very few accurate and relevant information is available on the fracture toughness of both joining types. The presented research work consists of three main parts. - Main theoretical background on stiffness, strength and fracture characteristics of the considered joint types. - Mode I and II testing of hybrid adhesive bonded/spot welded specimen to retrieve force-displacement data and virtual testing based on finite element (FE) modelling. - Uncertainty quantification between experimental and virtual work. In general, the mode II tests correspond well with real test data. This cannot be concluded for the mode I tests. The flexibility of the double U–type samples (KS2) is difficult to simulate accurately, particularly from the point when first damage occurs. For both, the experimental and virtual data, the hybrid adhesive/spot welded joints showed the highest maximum force.